Knock down of p53 or its ubiquitin ligase E6AP does not affect the sensitivity of human papillomavirus-positive cervical cancer cells to cisplatin - Michnov, Olga (e-Century Publishing Corporation, 2012)
The persistent infection with high risk human papillomaviruses (hrHPV) is a necessary risk factor for the development of cervical cancer, which is the second most frequent cancer in women worldwide. Cisplatin-based radiotherapy represents the current treatment regimen. However, the results for advanced and recurrent disease are far from optimal. Since almost all cervical cancers contain wild type (wt) p53, which is degraded by the complex of hrHPV E6 and the ubiquitin ligase E6AP, we addressed if the reconstitution of p53 via silencing of E6AP sensitizes cervical cancer cells towards cisplatin treatment. For this we established and characterized two novel cervical cancer cell lines that contain integrated HPV16 genomes. Long-term established HeLa and SiHa cells and the novel cervical cancer cell lines at low passage numbers were treated with different concentrations of cisplatin. Cell viability was measured by the WST-1 assay. In addition, single cisplatin treatment was combined with the silencing of E6AP or p53. The comparison to HeLa and SiHa cells revealed a higher sensitivity of the novel cell lines to cisplatin treatment, which caused p53 accumulation and transcriptional induction of p21. Silencing of E6AP further increased p53 protein levels, but had no effect on cell viability when combined with cisplatin treatment. Interestingly, silencing of p53 had also no effect. We therefore conclude that reactivation of p53 via silencing of E6AP does not increase the sensitivity of cervical cancer cells towards cisplatin treatment.